Penguatan Nilai Karakter Melalui Pembelajaran Akidah Akhlak Di Madrasah - Syarifah Aulia Rabbani; Abdul Quddus; Hilmiati; Yudhi Setiawan (Cetta: Jurnal Ilmu Pendidikan, 2023)
One of the most effective means for reinforcing and developing noble character in students whose role is to guide students in understanding and practicing Islamic teachings is through religious education. This study aims to determine the reinforcement strategy of character values ​​in learning aqidah morals at MIN 1 Mataram. This type of research uses descriptive qualitative research. Research data obtained through observation, interviews, and documentation techniques. The data analysis technique uses data reduction, data display and conclusion drawing, while the data validation technique used is increasing persistence and triangulation. The results of this study state that the internalizing character values ​​in teaching aqeedah morals at MIN 1 Mataram is carried out by preparing lesson plans and internalizing character values ​​into the material.